Are important phenomena of joint production still being neglected by economic theory? A review of recent literature - Harald Dyckhoff; Rainer Souren (Journal of Business Economics, 2022)
Joint production is a term with a long history in economics, encompassing a variety of ubiquitous production types that usually generate both main products as well as desirable and undesirable byproducts. However, studies in economic history show that important phenomena subsumed under this term were largely ignored by the theories of general economics and of business economics in the twentieth century. Our systematic, narrative literature review based on the Web of Science analyses the extent to which this and other terms corresponding to such phenomena have been taken up by researchers since then. Whereas the number of papers on undesirable outputs has soared, especially in the past decade, the economic literature regarding joint production and harmless byproducts is much smaller and hardly growing. This is in stark contrast to their relevance in practice, recorded in the non-economic literature. Harmful byproducts result from coupled production, as a rule. However, this important manifestation of joint production is usually not distinguished from other specific types. In German-language literature, coupled production is defined as a kind of (truly) joint production in which an intended product cannot be manufactured without an additional type of output under consideration. Our review reveals a lack of clarity, precision, and consistency in the use of established terms and concepts in English-language literature, that may lead to insufficient external validity of widely accepted models. Moreover, one gets the impression that academic disciplines concerned with business or general economics focus too much on problems that are currently of economic interest, while neglecting other issues that may be marginal today but are likely to be of critical importance in the near future.
Keywords: B20; D24; D62; L11; L23; M11; Q53; 650; Pollution; Waste; By-product; External effect; Joint costs